2017
DOI: 10.1186/s13071-017-2111-y
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium and Giardia in Africa: current and future challenges

Abstract: Cryptosporidium and Giardia are important causes of diarrhoeal illness. Adequate knowledge of the molecular diversity and geographical distribution of these parasites and the environmental and climatic variables that influence their prevalence is important for effective control of infection in at-risk populations, yet relatively little is known about the epidemiology of these parasites in Africa. Cryptosporidium is associated with moderate to severe diarrhoea and increased mortality in African countries and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
209
7
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(236 citation statements)
references
References 314 publications
(383 reference statements)
18
209
7
2
Order By: Relevance
“…However, the infection is common, and determining any change due to climate may be difficult. Both Giardia and Cryptosporidium are common in developing countries, and include a variety of species and types, and it has been suggested that climate change will increase malnutrition and contamination of water sources [145].…”
Section: Protozoamentioning
confidence: 99%
“…However, the infection is common, and determining any change due to climate may be difficult. Both Giardia and Cryptosporidium are common in developing countries, and include a variety of species and types, and it has been suggested that climate change will increase malnutrition and contamination of water sources [145].…”
Section: Protozoamentioning
confidence: 99%
“…Having a developing immune system, being undernourished, and animal contact are risk factors for intestinal parasite infection [2,7,8]. Symptoms of intestinal parasites can include lack of appetite, anemia, abdominal pains, cognitive impairment, fever, vomiting, malabsorption, and diarrhea [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Humans can be infected through ingesting water and food contaminated with G. duodenalis cysts [6]. e clinical symptoms of giardiasis are diarrhea, dehydration, abdominal pain, nausea, vomiting, and weight loss [2,6,7]. Giardiasis caused by G. duodenalis also has been recognized as an important zoonotic disease for both public and animal health [2,7,8].…”
Section: Introductionmentioning
confidence: 99%